2018
DOI: 10.1108/ijem-10-2017-0294
|View full text |Cite
|
Sign up to set email alerts
|

Creativity nurturing behaviour scale for teachers

Abstract: Purpose Today, innovation and creativity are the buzz words in the galore of not only business but also of education. The need to foster creativity and innovation has long been a priority in the educational and corporate spheres. The purpose of this paper is to propose the scale for the measurement of teacher’s creativity nurturing behaviour. Design/methodology/approach The sample consists of 356 primary school teachers from various category, e.g. municipal schools, private schools, Indian Certificate Second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 50 publications
1
22
1
1
Order By: Relevance
“…These are specific business competencies that characterise critical thinking as applied in business settings. More recently, however, it has been associated with entrepreneurship (Deale 2016; Verzat, O'Shea, and Jore 2017), creativity and innovation (Sharma and Sharma 2018;von der Heidt 2018).…”
Section: Conceptions Of Critical Thinking In Business Education (Rq2)mentioning
confidence: 99%
“…These are specific business competencies that characterise critical thinking as applied in business settings. More recently, however, it has been associated with entrepreneurship (Deale 2016; Verzat, O'Shea, and Jore 2017), creativity and innovation (Sharma and Sharma 2018;von der Heidt 2018).…”
Section: Conceptions Of Critical Thinking In Business Education (Rq2)mentioning
confidence: 99%
“…(2) Abstraction (e.g., "The students have opportunity to share their ideas and suggestions during the class"), (3) Critical Thinking (e.g., "To develop critical thinking, I enquire students about their idea"), and ( 4) Motivation ("I encourage students to learn the basics of the topic").In previous research, total scores demonstrated good reliability varying from .72 to .80 (Cronbach's alpha; Sharma & Sharma, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Teacher's Creativity Nurturing Behavior(TCNB)is a 15-item self-report measure (1 = totally disagree to 6 = totally agree)that assesses teacher's engagement in organizing educational context that facilitatescreative potential and creative behavior in schoolchildren (Sharma & Sharma, 2018).According to the results of prior research,TCNBhas a four-factor structure: (1) Inquisitiveness (e.g., "I question the students' ideas, to ponder them to explore it further"),…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations